2022
DOI: 10.3390/biology11121691
|View full text |Cite
|
Sign up to set email alerts
|

High-Risk Human Papillomavirus Infection in Lung Cancer: Mechanisms and Perspectives

Abstract: Lung cancer is a very prevalent and heterogeneous group of malignancies, and most of them are etiologically associated with tobacco smoking. However, viral infections have been detected in lung carcinomas, with high-risk human papillomaviruses (HR-HPVs) being among them. The role of HR-HPVs in lung cancer has been considered to be controversial. This issue is due to the highly variable presence of this virus in lung carcinomas worldwide, and the low viral load frequently that is detected. In this review, we ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 158 publications
0
6
0
1
Order By: Relevance
“…In light of the above-mentioned evidence [3,27,45], a similar mechanism, based on inflammation induced by air pollution [46], could explain the role of HPV in lung carcinogenesis among never-smoker patients, Figure 5.…”
Section: Hpv Infection Of Lung Cells: Pathogenesis Prevalence and Car...mentioning
confidence: 93%
See 3 more Smart Citations
“…In light of the above-mentioned evidence [3,27,45], a similar mechanism, based on inflammation induced by air pollution [46], could explain the role of HPV in lung carcinogenesis among never-smoker patients, Figure 5.…”
Section: Hpv Infection Of Lung Cells: Pathogenesis Prevalence and Car...mentioning
confidence: 93%
“…In light of the above-mentioned evidence [3,27,45], a similar mechanism, based on inflammation induced by air pollution [46], could explain the role of HPV in lung carcinogenesis among never-smoker patients, Figure 5. A recent study revealed that 16% of NSCLC patients presented circulating HPV-DNA in peripheral blood [47] and abnormally expressed miRNAs in HPV-associated tumors [47].…”
Section: Hpv Infection Of Lung Cells: Pathogenesis Prevalence and Car...mentioning
confidence: 93%
See 2 more Smart Citations
“…For example, human hepatitis B and C virus (HBV and HCV) infection increases the incidence of primary liver cancer; human papillomavirus (HPV) infection is associated with cervical and anal genital cancers; Epstein-Barr virus (EBV) is associated with the development of nasopharyngeal and lymphatic cancers; and Helicobacter pylori (HP) significantly increases the risk of gastric cancer. Similarly, emerging pathogens have been found that cause high-risk lung cancer, such as high-risk human papillomaviruses (HR-HPVs), cytomegalovirus, influenza virus, and measles virus (MV) [9][10][11][12]. In addition, accumulating studies have revealed the correlation of specific microbiota with lung cancer, such as Firmicutes, Proteobacteria, Actinobacteria, and Veillonella [13][14][15].…”
mentioning
confidence: 99%